Cover Picture: Biotechnology Journal 12/2017. Issue 12 (18th December 2017) - Unknown
Abstract : Biomaterials such as chitosan, a derivative from the chitin shells of crabs and other crustaceans, can promote single cells to merge and form multicellular spheroids when used as cell culture substrates. These multicellular spheroids show promises in the field of regenerative medicine, especially in cartilage repair, nerve regeneration, and blood vessel formation. The cover is prepared by Ting‐Chen Tseng, Chui‐Wei Wong, Fu‐Yu Hsieh and Shan‐hui Hsu, authors of the article "Biomaterial Substrate‐Mediated Multicellular Spheroid Formation and Their Applications in Tissue Engineering" (https://doi.org/10.1002/biot.201700064 ).